Centrum voor Levens- en Gezinsvragen Leuven. Activiteitenverslag... (Leuven: CLG Leuven)
"Fonds Suzan Daniel (FSD)Periodiciteit : (twee)jaarlijksRedactie : Ridderstraat 149, 3000 Leuven; vanaf (199?) Diestsesteenweg 33, 3010 Kessel-Lo"